Women in the Weimar Republic - Boak, Helen (Book collections on Project MUSE., 2013)
This book is the first comprehensive survey of women in the Weimar Republic, exploring the diversity and multiplicity of women's experiences in the economy, politics and society. Taking the First World War as a starting point, this book explores the great changes in the lives, expectations, and perceptions of German women, with new opportunities in employment, education and political life and greater freedoms in their private and social life, all played out in the media spotlight. Engaging with the most recent research and debates, this book portrays the Weimar Republic as a period of progressive change for young, urban women, to be stalled in 1933. This book will be essential reading for students and researchers of German women in the early twentieth century, and will also appeal to anyone interested in the Weimar Republic and women's history.